Identification of Rabbit Myostatin Gene Polymorphisms - Tya I Amalianingsih; B. Brahmantiyo; . Jakaria (Media Peternakan, 2015)
The existence of selection on the rabbits with potential for meat has only been seen from phenotypic aspects including performance and productivity, while the molecular genetic studies are still very rare. One of the candidate genes for meat production traits in rabbit is myostatin. Totally 50 blood samples of male rabbits from Rex, Satin, Reza (crossing from Rex and Satin), Flemish Giant and FZ3 (crossing from Flemish Giant and Reza) breed were used at Indonesian Research Institute for Animal Production (IRIAP). Genetic polymorphism by Polymerase Chain Reaction – Restriction Fragment Length Polymorphism (PCR-RFLP) method used FspBI restriction enzyme. PCR-RFLP data were analyzed by calculating allele and genotype frequencies. Sequencing was performed in rabbit with different genotypes which represents each of the samples. Genotype of AT had two cut points of the FspBI restriction enzyme at the base position of 508 bp and 444 bp. The cut point at the base position of 446 bp was site mutation base T became A. Genotype of TT had one cut point at the base position of 508 bp and no mutation site. Allele T had higher frequency than allele A and just Rex and Reza rabbit breeds had two alleles. The other rabbits (Satin, Flemish Giant and FZ3) only had one allele i.e., allele T. PCR - RFLP analysis of the MSTN|FspBI gene segments was polymorphic in Rex and Reza rabbit breeds. All of rabbit breeds in this study did not have AA genotype.Key words: myostatin gene, rabbit